Peran Integral Perbedaan Individual terhadap Hubungan antara Self Efficacy dan Work Related Performance: Sebuah Telaah Kritis - Anatan, Lina (Kajian Manajemen dan Bisnis, 2011)
This paper discusses a critical review of an article written by Judge et al. (2007) entitled "Self-Efficacy and Work Related Performance: The Integral Role Of Individual Differences." The objective of the study was to examine the contribution of self-efficacy on work performance which is controlled by personality specifically The Big Five Traits, intelligence or general mental ability, and the experience of doing work or tasks. The study is interesting to review because it was a meta-analysis study that focused on conceptual relationship amongst self efficacy, individual difference, and work-related performance, and the possibility of relationship amongst the existing variables to examine the joint influence in work performance. There are few studies on the joint influence amongst the variables in the literature of industrial psychology and organization. Therefore this study is expected to explain the contribution of self-efficacy, general mental ability, and personality specifically the Big Five Traits, and experience to estimate work related performance.